Pelaksanaan Pertanggung Jawaban Pidana Terhadap Tindak Pidana Penganiayaan Yang Menyebabkan Meninggal Dunia Yang Dilakukan Oleh Orang Yang Cacat Jiwanya Di Wilayah Hukum Pengadilan Negeri Kabanjahe - Supriyono Ginting; Rika Lestari; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Crimeisan actisun law fultointentionally have been done by some one who is accountable for his actions, expressed as punishable. Crime also certain acts, asmisconduct orviolation of law. Crime is the result of interaction because of the interrelation between the existing and influence each other. Crimes against life lately tends to increase. Crimes against life is indeed a symptom of a very disturbing tranquility, peace and tranquility of the community, especially Tanah Karo. In this case the role of law enforcement is essentialing ivesasense of justice to the community. The purpose of this paper is; First, to determine the implementation of criminal responsibility for the crimes of persecution that causes death is done by people who Disabilities soulin the District Court Jurisdiction Kabanjahe. Second, to determine the barriers in the implementation of criminal responsibility for the crimes of persecution that causes death is done by people who Disabilities soul in the District Court Jurisdiction Kabanjahe. Third, to determine the efforts made in the implementation of criminal responsibility for the crimes of persecution that causes death is done by people who Disabilities soul in the District Court Jurisdiction Kabanjahe.This type of research is the study of law sociological or empirical jurisdiction. Location of the study is Kabanjahe District Court Jurisdiction. Sources of data,supported by the primary data source, secondary data sources, tertiary data sources, while data collection techniq ues are interviews/interviews and review of literature. Having collected data was then analyzed qualitatively using the deductive method of analyzing the problems of a general nature and the ndrawn the conclusion exclusively based on existing theory. From the results of the research problem, there are three things that can be concluded, first, to determine the implementation of criminal responsibility for the crimes of persecution that causes death is done by people who Disabilities soul in the District Court Jurisdiction Kabanjahe difficult because of the barriers faced by law enforcementyan. Second, the barriers faced by law enforcement in the jurisdiction of the district Court Kabanjahe; culture,or customs of ficials who have a hereditary, funding issues, and the lack of law enforcement of ficerspeofesionalisme. And prevention effort sunder taken by law enforcement in the region District Court Kabanjahe is; law enforcement professional and high integrity, cooperation with actors on funding family psychiatric examination of fender, the presence of a dequatein frastructure and facilities.